Electrode material and preparation method and preparation system thereof
By coating the metal etching reaction liquid on the conductive substrate network using slit extrusion, and performing in-situ thermal decomposition and high-temperature modification treatment, the problem of the amount and waste of reaction liquid in the electrolytic water hydrogen-making electrode material is solved, and high-performance and stable electrode material preparation is achieved.
Patent Information
- Application Number
- CN202510149115.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-25
AI Technical Summary
In the industrial production of electrolytic water hydrogen production electrode materials, it is difficult to effectively reduce the amount and waste of reaction liquid, while ensuring the high performance and stability of the electrode materials.
By coating the metal etching reaction liquid on both sides of the conductive base grid using slit extrusion, performing the etching reaction, in-situ thermal decomposition is performed, forming a conductive base grid-metal heterolayer composite, and applying the cast film reaction liquid on the surface of the heterolayer for high-temperature modification, high-performance electrode material is prepared.
It effectively reduces the amount and waste of reaction liquid, improves the catalytic performance and stability of the electrode material, and reduces the electrode potential.
Smart Images

Figure BDA0005268426110000131 
Figure BDA0005268426110000132 
Figure BDA0005268426110000142
Abstract
Description
Technical Field
[0001] The present invention relates to the field of hydrogen energy technology, and in particular to an electrode material and a preparation method and a preparation system thereof. Background Art
[0002] Water electrolysis hydrogen production technology is an important carrier for the future development of green energy and low-carbon economy. In order to continuously reduce the production cost of green hydrogen produced by water electrolysis, we should pay attention to the research and development of high-performance and stable water electrolysis electrode materials, give full play to the characteristics of high electrical density, low energy consumption and long life, and reduce the equipment volume and energy input of large-scale electrolyzers, so as to achieve the purpose of reducing costs and increasing efficiency.
[0003] The mainstream alkaline water electrolysis hydrogen production technology in my country is mainly traditional alkaline water electrolysis hydrogen production (ALK), in which the required water electrolysis hydrogen production electrodes are mostly self-supporting electrodes after the conductive base network and its loaded catalytic layer, which have the advantages of high mechanical strength and good mass transfer effect. High-performance self-supporting electrode materials are the core components that affect the ALK water electrolysis hydrogen production effect. At present, there are a large number of methods for preparing self-supporting water electrolysis catalysts, such as hydrothermal method, electrodeposition method, sol-gel method, high-temperature reduction method, thermal spraying method, corrosion engineering method, immersion growth method, etc. However, when it comes to the field of industrial production, there are few reports on the ability to produce water electrolysis hydrogen production electrodes with both high activity and good stability at a faster speed and efficient material utilization. For example, the prior art provides a method of using a nickel-based metal solution to load a catalytic layer in an infiltration manner to prepare an electrode material, which is suitable for an industrial roll-to-roll production method. Although this method improves production efficiency, the production method requires a large amount of metal reaction solution to participate in the reaction to ensure sufficient infiltration of the conductive base mesh, and the conductive base mesh is usually subjected to conventional pretreatments such as acid washing or alkali washing. In the subsequent infiltration process, the reaction liquid will gradually be contaminated due to the accumulation effect of these pretreatment solutions, resulting in a large amount of reaction liquid being ultimately wasted. At the same time, the conductive base mesh after infiltration will experience excess reaction liquid aggregation and dripping during the coating process, and this part of the reaction liquid usually does not participate in the reaction again, seriously affecting the recycling availability of the reaction liquid.
[0004] In summary, how to effectively reduce the amount of reaction solution and avoid waste of reaction solution while ensuring the performance of electrode materials has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] The object of the present invention is to provide an electrode material and a preparation method and a preparation system thereof. The preparation method provided by the present invention can effectively reduce the amount of raw material reaction liquid used, avoid pollution and waste of reaction liquid, and effectively improve the recycling rate; at the same time, it can effectively improve the catalytic performance of the electrode material and reduce the electrode potential.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention also provides a method for preparing an electrode material, comprising the following steps:
[0008] (1) coating a metal etching reaction solution on both sides of the conductive base mesh by a slit extrusion method and then performing an etching reaction to obtain a conductive base mesh-metal precursor composite;
[0009] (2) subjecting the conductive base mesh-metal precursor composite obtained in step (1) to in-situ thermal decomposition to obtain a conductive base mesh-metal heterogeneous layer composite;
[0010] (3) coating the surface of the conductive base mesh-metal heterogeneous layer composite obtained in step (2) with a film casting reaction solution to obtain a film-forming composite;
[0011] (4) subjecting the biofilm-forming complex obtained in step (3) to high-temperature modification to obtain an electrode material.
[0012] Preferably, the extrusion volume of the slit extrusion in step (1) is 0.1 to 50 L / min; and the running speed of the conductive base mesh is 0.1 to 5 m / min.
[0013] Preferably, the coating thickness of the metal etching reaction solution in step (1) is 50 to 250 μm.
[0014] Preferably, the metal etching reaction solution in step (1) comprises a metal salt and a self-thermal decomposition agent; the molar ratio of the metal salt to the self-thermal decomposition agent is (1.3-2):(0.2-3); and the pH of the metal etching reaction solution is 1.0-3.0.
[0015] Preferably, the metal salt is a mixture of one or more of lanthanum nitrate, cerium nitrate, nickel nitrate, manganese nitrate, chromium nitrate, zirconium nitrate, cobalt nitrate, copper nitrate, vanadium nitrate and zinc nitrate and an iron salt; the iron salt is one or more of ferric nitrate, ferric chloride, ferric sulfate, ferric perchlorate and ferric dihydrogen phosphate; the self-thermal decomposition agent is one or more of cyanamide, glycerol, ethylene glycol, glucose, chitosan, polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide.
[0016] Preferably, the ratio of the total amount of one or more of lanthanum nitrate, cerium nitrate, nickel nitrate, manganese nitrate, chromium nitrate, zirconium nitrate, cobalt nitrate, copper nitrate, vanadium nitrate and zinc nitrate in the metal salt to the amount of the iron salt is 1:(0.3-1).
[0017] Preferably, the film casting reaction liquid in step (3) is an aqueous solution of one or more of sodium phosphate, phosphoric acid, sodium hypophosphite, sodium dihydrogen phosphate, sodium borate, sodium tungstate, and ammonium molybdate.
[0018] Preferably, in the step (3), the molar concentration of each solute in the film casting reaction solution is independently 1 to 100 mM, and the pH of the film casting reaction solution is 3.0 to 8.0.
[0019] The present invention also provides an electrode material prepared by the preparation method described in the above technical solution, comprising a metal heterogeneous layer and a protective layer symmetrically arranged in sequence on both sides of a conductive base network.
[0020] The present invention also provides a preparation system used in the preparation method described in the above technical solution, comprising a winding drum, an etching treatment unit, a medium-temperature thermal decomposition channel furnace and a high-temperature thermal treatment channel furnace connected in sequence; the etching treatment unit comprises an etching liquid coating unit, an etching reaction liquid circulation treatment unit and a low-temperature etching channel furnace arranged in sequence;
[0021] The etching liquid coating unit comprises a slit extrusion device and an etching reaction liquid storage tank.
[0022] The present invention provides a method for preparing an electrode material, comprising the following steps: (1) coating both sides of a conductive base mesh with a metal etching reaction liquid by a slit extrusion method and then performing an etching reaction to obtain a conductive base mesh-metal precursor composite; (2) performing in-situ thermal decomposition on the conductive base mesh-metal precursor composite obtained in the step (1) to obtain a conductive base mesh-metal heterogeneous layer composite; (3) coating the surface of the conductive base mesh-metal heterogeneous layer composite obtained in the step (2) with a film casting reaction liquid to obtain a film-forming composite; and (4) performing a high-temperature modification treatment on the film-forming composite obtained in the step (3) to obtain an electrode material. The present invention makes the etching reaction liquid adhere to the conductive base net by coating, so as to control the amount of reaction liquid used and avoid the waste of a large amount of reaction liquid caused by immersion treatment; at the same time, the reaction liquid is coated by slit extrusion, so as to further control the coating amount of the reaction liquid and avoid the waste of reaction liquid by dripping, and the slit extrusion method greatly reduces the contact between the reaction liquid and the conductive base net and the outside world, avoids the pollution waste of the reaction liquid, and effectively reduces the amount of reaction liquid used; the coating method makes the reaction liquid evenly distributed on the conductive base net, and effectively improves the performance of the electrode material; the metal hydroxide transition layer obtained by the etching reaction on the conductive base net is converted by in-situ thermal decomposition to obtain a metal hydroxide-oxide heterogeneous layer, which is conducive to electron transfer, and forms a microporous structure in the heterogeneous layer, increases the specific surface area, effectively improves the mass transfer effect of the electrode material and enhances the catalytic performance; the casting reaction liquid is coated on the surface of the heterogeneous layer and subjected to high-temperature modification, so as to activate the surface structure of the heterogeneous layer and age the surface of the heterogeneous layer, avoid physical detachment and chemical corrosion of the electrode material, effectively improve the stability of the electrode material, and finally effectively reduce the amount of reaction liquid used and improve the catalytic performance of the electrode material. The results of the examples show that the method for preparing the electrode material provided by the present invention effectively reduces the amount of reaction solution used, and the performance of the electrode material obtained by recycling the reaction solution is stable, thus avoiding pollution and waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A system for preparing an electrode material in Example 1, wherein 1 is a winding drum, 2 is an etching treatment unit, 2-1 is an etching liquid coating unit, 2-2 is an etching reaction liquid circulation treatment unit, 2-3 is a low-temperature etching channel furnace, 3 is a medium-temperature thermal decomposition channel furnace, 4 is a high-temperature heat treatment channel furnace, 5 is a cooling treatment unit, 6 is a collection winding drum, 7 is an exhaust gas collection channel, and 8 is a film casting reaction liquid coating device;
[0024] Figure 2 is the electrolysis potential of the electrode material prepared when the metal etching reaction solution in Example 2 is recycled for different times;
[0025] Figure 3 is the electrolysis potential of the electrode material prepared when the metal etching reaction solution in Example 3 is recycled for different times;
[0026] Figure 4 The electrolysis potential of the electrode material prepared when the metal etching reaction solution of Example 4 is recycled for different times;
[0027] Figure 5 It is the electrolysis voltage of the electrode material prepared when the metal etching reaction solution in Example 3 and Comparative Example 1 is recycled once. DETAILED DESCRIPTION
[0028] The present invention also provides a method for preparing an electrode material, comprising the following steps:
[0029] (1) coating a metal etching reaction solution on both sides of the conductive base mesh by a slit extrusion method and then performing an etching reaction to obtain a conductive base mesh-metal precursor composite;
[0030] (2) subjecting the conductive base mesh-metal precursor composite obtained in step (1) to in-situ thermal decomposition to obtain a conductive base mesh-metal heterogeneous layer composite;
[0031] (3) coating the surface of the metal heterogeneous layer in the conductive base mesh-metal heterogeneous layer composite obtained in step (2) with a film casting reaction liquid to obtain a film-forming composite;
[0032] (4) subjecting the biofilm-forming complex obtained in step (3) to high-temperature modification to obtain an electrode material.
[0033] The present invention coats a metal etching reaction liquid on a conductive base net by a slit extrusion method and then performs an etching reaction to obtain a conductive base net-metal precursor composite material.
[0034] As an embodiment of the present invention, the conductive base mesh can be a nickel mesh, a stainless steel mesh, a copper mesh, a nickel-iron alloy mesh, a titanium mesh or a carbon fiber woven mesh, or a nickel mesh or a nickel-iron alloy mesh. In the present invention, the conductive base mesh serves as a matrix of the electrode material to support the reaction solution to avoid the dripping and waste of the reaction solution; at the same time, it supports the active ingredients of the electrode material to further improve the performance of the electrode material; by limiting the type of the conductive base mesh, the role of the conductive base mesh is fully utilized, the amount of the reaction solution is further reduced and the performance of the electrode material is improved.
[0035] As an embodiment of the present invention, the metal etching reaction liquid may include a metal salt and a self-thermal decomposition agent; the metal salt may be a mixture of one or more of lanthanum nitrate, cerium nitrate, nickel nitrate, manganese nitrate, chromium nitrate, zirconium nitrate, cobalt nitrate, copper nitrate, vanadium nitrate and zinc nitrate and an iron salt; the iron salt may be one or more of iron nitrate, iron chloride, iron sulfate, iron perchlorate and ferrous dihydrogen phosphate; the self-thermal decomposition agent may be one or more of cyanamide, glycerol, ethylene glycol, glucose, chitosan, polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide. In the present invention, by limiting the specific types of each component in the metal etching reaction liquid, the performance of the etching reaction liquid is effectively improved, which is conducive to the close contact between the metal etching reaction liquid and the conductive base network.
[0036] As an embodiment of the present invention, the molar ratio of the metal salt and the self-thermal decomposition agent can be (1.3-2):(0.2-3), or (1.5-1.8):(0.4-2), or (1.6-1.7):(0.8-1); the molar ratio of one or more of lanthanum nitrate, cerium nitrate, nickel nitrate, manganese nitrate, chromium nitrate, zirconium nitrate, cobalt nitrate, copper nitrate, vanadium nitrate and zinc nitrate in the metal salt to the molar ratio of the iron salt can be 1:(0.3-1), or 1:(0.5-0.8), or 1:(0.6-0.7); the pH of the metal etching reaction solution can be 1.0-3.0; the pH of the metal etching reaction solution can be adjusted by acid; the acid can be hydrochloric acid, sulfuric acid or nitric acid. In the present invention, by limiting the composition and pH value of the metal etching reaction liquid, regulating the viscosity and performance of the etching reaction liquid, the conductive base network can be fully in contact with the etching reaction liquid, avoiding dripping and waste of the etching reaction liquid, further reducing the amount of reaction liquid used and improving the catalytic performance of the electrode material.
[0037] As an embodiment of the present invention, the slit width of the slit extrusion can be 10-500 μm, 50-400 μm, or 200-300 μm; the extrusion volume of the slit extrusion can be 0.1-50 L / min, 1-40 L / min, or 20-30 L / min; the running speed of the conductive base net can be 0.1-5 m / min, 0.5-3 m / min, or 1-2 m / min. In the present invention, by limiting the process parameters of the slit extrusion, the coating amount can be effectively controlled, the etching reaction liquid and the conductive base net can be in close contact, and the dripping waste of the etching reaction liquid and the pollution waste of the etching reaction liquid can be avoided; at the same time, the reaction liquid may still drip under the action of gravity, but when the coating is carried out by the slit extrusion coating method, the etching reaction liquid will not be contaminated by the conductive base net, and the dripping reaction liquid can be collected and recycled for further use, thereby further reducing the amount of metal etching reaction liquid.
[0038] As an embodiment of the present invention, the coating is performed on both sides of the conductive base mesh. In the present invention, by limiting the coating position, the etching reaction liquid is evenly distributed on the conductive base mesh, and the metal etching reaction liquid covers the conductive base mesh, effectively reducing the dripping of the metal etching reaction liquid and further reducing the amount of reaction liquid.
[0039] As an embodiment of the present invention, the coating thickness of the metal etching reaction liquid can be 50-250 μm, 80-200 μm, or 100-150 μm. In the present invention, by limiting the coating thickness of the metal etching reaction liquid, it is possible to achieve close contact between the metal etching reaction liquid and the conductive base network, and avoid excessive use of the metal etching reaction liquid, resulting in waste.
[0040] As an embodiment of the present invention, the temperature of the etching reaction can be 50-100°C, 60-90°C, or 70-80°C; the time of the etching reaction can be 5-60 minutes, 10-50 minutes, or 20-30 minutes. In the present invention, during the etching reaction, a reduction-oxidation reaction occurs between the iron ions in the etching reaction solution and the conductive base network. As the etching reaction proceeds, the water in the etching reaction solution continues to evaporate, the solute components in the etching reaction solution gradually increase in concentration, and a multi-metal hydroxide catalyst layer is in situ grown on the surface of the conductive base network; by limiting the temperature of the etching reaction, the etching reaction is fully carried out, and the performance of the electrode material is further improved.
[0041] After obtaining the conductive base mesh-metal precursor composite material, the present invention performs in-situ thermal decomposition on the conductive base mesh-metal precursor composite material to obtain a conductive base mesh-metal heterogeneous layer composite material.
[0042] As an embodiment of the present invention, the temperature of the in-situ thermal decomposition can be 150-300°C, 180-280°C, or 200-250°C; the time of the in-situ thermal decomposition can be 10-60 minutes, 15-50 minutes, or 20-30 minutes. In the present invention, during the in-situ thermal decomposition process, the organic matter in the metal etching reaction liquid spontaneously burns, generates heat and gas, and converts the metal hydroxide catalytic layer into a metal hydroxide-oxide heterogeneous layer, while forming a microporous structure in the heterogeneous layer; by limiting the temperature of the in-situ thermal decomposition, the in-situ thermal decomposition reaction is promoted, and the catalytic performance of the electrode material is further improved.
[0043] After obtaining the conductive base net-metal heterogeneous layer composite material, the present invention coats the film casting reaction liquid on the surface of the conductive base net-metal heterogeneous layer composite material to obtain a film-forming composite material.
[0044] As an embodiment of the present invention, the casting reaction liquid can be an aqueous solution of one or more of sodium phosphate, phosphoric acid, sodium hypophosphite, sodium dihydrogen phosphate, sodium borate, sodium tungstate, and ammonium molybdate. In the present invention, by limiting the composition of the casting reaction liquid, the performance of the casting reaction liquid can be improved, and the performance of the electrode material can be further improved.
[0045] As an embodiment of the present invention, the molar concentration of each solute in the film casting reaction solution can be independently 1 to 100 mM, 2 to 50 mM, or 10 to 25 mM; the pH value of the film casting reaction solution can be 3.0 to 8.0, 3.5 to 6.5, or 4 to 5. In the present invention, by limiting the process parameters of the film casting reaction solution, the performance of the film casting reaction solution is improved, the modification of the heterogeneous layer is achieved, and the catalytic performance and stability of the electrode material are further improved.
[0046] As an embodiment of the present invention, the coating can be applied on both sides of the conductive base mesh-metal heterogeneous layer composite material. In the present invention, by limiting the coating position, the casting reaction liquid is evenly distributed on the conductive base mesh, and the casting reaction liquid fully modifies the heterogeneous layer, further improving the catalytic performance of the electrode material.
[0047] As an embodiment of the present invention, the coating thickness of each layer of the casting reaction liquid is 50 to 250 μm, or 80 to 200 μm, or 100 to 150 μm. In the present invention, the casting reaction liquid is coated on the surface of the metal hydroxide-oxide heterogeneous layer, so that the active layer of the heterogeneous layer structure and the acid anions of the casting reaction liquid undergo a nucleation reaction, and a metal salt with a low solubility product constant is generated in situ to form a skin layer, which helps to improve the electronic structure of the heterogeneous layer and further improve the electrocatalytic performance; at the same time, a stable skin layer structure is obtained, which further improves the stability of the electrode material.
[0048] After obtaining the biofilm composite, the present invention performs high-temperature modification treatment on the biofilm composite to obtain the electrode material.
[0049] As an embodiment of the present invention, the temperature of the high temperature modification treatment can be 300-900°C, 350-600°C, or 400-500°C; the time of the high temperature modification treatment can be 30-200 minutes, 50-150 minutes, or 100-120 minutes. In the present invention, the biofilm composite is subjected to high temperature modification treatment to achieve further aging treatment of the skin layer structure, increase the degree of crystallization, further improve the protective performance of the skin layer, and further improve the stability of the electrode material.
[0050] As an embodiment of the present invention, the high-temperature modification treatment can be carried out in one or more atmospheres selected from argon, nitrogen, air, ammonia, carbon-containing atmosphere, sulfur-containing atmosphere and phosphorus-containing atmosphere. In an embodiment of the present invention, the carbon-containing atmosphere can be specifically methane, acetonitrile or dicyandiamide; the sulfur-containing atmosphere can be specifically sulfur, hydrogen sulfide or thioacetamide; the phosphorus-containing atmosphere can be specifically sodium hypophosphite. In the present invention, the atmosphere for the high-temperature modification treatment can be selected according to actual needs to effectively improve the performance of the electrode material; by limiting the type of atmosphere for the high-temperature modification treatment, the modification treatment of the skin layer structure can be effectively adjusted to further improve the performance of the electrode material.
[0051] The preparation method provided by the present invention coats the reaction liquid by slit extrusion, controls the coating amount of the reaction liquid, avoids dripping and waste of the reaction liquid, and the slit extrusion method greatly reduces the contact between the reaction liquid and the conductive base network and the outside world, avoids pollution and waste of the reaction liquid, and effectively reduces the amount of reaction liquid; at the same time, the catalytic layer formed by etching the reaction liquid is modified, effectively improving the catalytic performance of the electrode material and reducing the electrode voltage.
[0052] The present invention also provides an electrode material prepared by the preparation method described in the above technical solution, comprising a metal heterogeneous layer and a protective layer symmetrically arranged in sequence on both sides of a conductive base network.
[0053] The metal heterogeneous layer in the electrode material provided by the present invention can promote electron transfer and effectively improve the electrocatalytic performance; the protective layer protects the electrode material to prevent physical shedding or chemical corrosion of the electrode material, effectively improving the stability of the electrode material, so that the electrode material can maintain stable and excellent catalytic performance and effectively reduce the electrode voltage.
[0054] The present invention also provides a preparation system used in the preparation method described in the above technical solution, comprising a winding drum, an etching processing unit, a medium-temperature thermal decomposition channel furnace and a high-temperature heat treatment channel furnace connected in sequence;
[0055] The etching processing unit comprises an etching liquid coating unit, an etching reaction liquid circulation processing unit and a low-temperature etching channel furnace which are arranged in sequence;
[0056] The etching liquid coating unit comprises a slit extrusion device and an etching reaction liquid storage tank.
[0057] like Figure 1 As shown, in the present invention, the preparation system comprises a winding drum 1. In the present invention, the winding drum is used to support the conductive base mesh, so that the continuous production of electrode materials can be achieved.
[0058] The present invention has no special limitation on the specifications of the winding drum, and any winding drum commonly used by those skilled in the art may be used.
[0059] like Figure 1 As shown, in the present invention, the preparation system also includes an etching processing unit 2 connected to the winding drum 1; the etching processing unit 2 includes an etching liquid coating unit 2-1, an etching reaction liquid circulation processing unit 2-2 and a low-temperature etching channel furnace 2-3 which are arranged in sequence.
[0060] like Figure 1 As shown, in the present invention, the etching liquid coating unit 2-1 includes a slit extrusion device and an etching reaction liquid storage tank. In an embodiment of the present invention, the etching reaction liquid storage tank and the slit extrusion device are connected through a pipeline valve.
[0061] like Figure 1 As shown, in an embodiment of the present invention, one side of the etching reaction liquid circulation treatment unit 2-2 is connected to the slit extrusion device through a pipeline valve member; the other side of the etching reaction liquid circulation treatment unit 2-2 is connected to the etching reaction liquid storage tank through a self-priming pump. In the present invention, by limiting the connection mode between the etching liquid coating unit and the etching reaction liquid circulation treatment unit, the metal etching reaction liquid dripping from the slit extrusion device coated on the surface of the conductive base mesh is collected and reused, so as to realize the circulation treatment of the metal etching reaction liquid, greatly reduce the amount of metal etching reaction liquid, and avoid the pollution and waste of the metal etching reaction liquid.
[0062] As an embodiment of the present invention, the etching reaction liquid circulation processing unit can detect the metal etching reaction liquid and replenish new metal etching reaction liquid according to actual needs. In the present invention, the collected metal etching reaction liquid is detected by the etching reaction liquid circulation processing unit, and new etching reaction liquid is replenished in time to ensure the stability of electrode material performance.
[0063] In an embodiment of the present invention, the two slit dies of the slit extrusion device can be arranged relative to each other. As an embodiment of the present invention, the conductive base mesh can pass through the middle of the two slit dies in a vertical or horizontal manner; the slit width of the slit extrusion device is 10 to 500 μm, or 50 to 400 μm, or 200 to 300 μm; the distance between the slit extrusion device and the conductive base mesh can be 0.1 to 2 mm, or 0.5 to 1.8 mm, or 1 to 1.5 mm. In the present invention, by limiting the setting position of the slit extrusion device, uniform coating of the metal etching reaction liquid is achieved, and the catalytic performance of the electrode material is further improved while reducing the amount of metal etching reaction liquid.
[0064] like Figure 1 As shown, in the present invention, the preparation system further includes a medium-temperature thermal decomposition channel furnace 3 connected to the etching processing unit 2 .
[0065] like Figure 1 As shown, in an embodiment of the present invention, the preparation system further includes a film casting reaction liquid coating device 8 connected to the medium-temperature thermal decomposition channel furnace 3. As an embodiment of the present invention, the film casting reaction liquid coating device can coat the film casting reaction liquid by slit extrusion; the two slit dies in the film casting reaction liquid coating device can be arranged relatively to each other, and the conductive base mesh-metal heterogeneous layer composite material can pass through the middle of the two slit dies in a horizontal manner. In the present invention, by limiting the position and coating method of the film casting reaction liquid coating device, uniform coating of the film casting reaction liquid is achieved, which promotes the sufficient modification of the conductive base mesh-metal heterogeneous layer composite material by the film casting reaction liquid, and further improves the catalytic performance of the electrode material.
[0066] like Figure 1 As shown, in the present invention, the preparation system also includes a high-temperature heat treatment channel furnace 4 connected to the film casting reaction liquid coating device 8.
[0067] like Figure 1As shown, in the embodiment of the present invention, the low temperature etching channel furnace 2-3, the medium temperature thermal decomposition channel furnace 3 and the high temperature heat treatment channel furnace 4 are provided with horizontal or vertical directional wheels; the number of directional wheels in the low temperature etching channel furnace is 3 to 10 pairs; the number of directional wheels in the medium temperature thermal decomposition channel furnace is 8 to 50 pairs; the number of directional wheels in the high temperature heat treatment channel furnace is 8 to 50 pairs. In the present invention, by limiting the arrangement mode and number of directional wheels, the time of the conductive base mesh in the corresponding channel furnace is controlled, and then the reaction time of the reaction occurring in the corresponding channel furnace is controlled, the corresponding reaction is fully carried out, and the catalytic performance of the electrode material is further improved.
[0068] In the embodiment of the present invention, the low temperature etching channel furnace 2-3, the medium temperature thermal decomposition channel furnace 3 and the high temperature heat treatment channel furnace 4 are provided with a waste gas collecting channel 7 with a one-way valve. In the present invention, by providing the waste gas collecting channel, the waste gas is discharged in time, which is conducive to full reaction and further improves the performance of the electrode material.
[0069] In an embodiment of the present invention, the high temperature heat treatment channel furnace rear 4 includes a cooling treatment unit 5 and a collecting winding drum 6 which are sequentially arranged. In the present invention, the cooling treatment unit is used to cool the prepared electrode material, which is convenient for the subsequent winding of the electrode material and is conducive to the continuous production of the electrode material; the collecting winding drum is used to wind the electrode material, which realizes the continuous production of the electrode material and effectively reduces the floor space occupied by the preparation system.
[0070] As an embodiment of the present invention, the production rate of the electrode material can be 25 to 1000 m 2 / h, and can also be determined by the specifications of the conductive base network and the equipment.
[0071] The preparation system provided by the present invention controls and recycles the amount of metal etching reaction liquid through a slit extrusion device and an etching reaction liquid circulation processing unit, thereby greatly reducing the amount of metal etching reaction liquid; by limiting the arrangement and number of directional wheels in the reactor, the corresponding reaction in the reactor is completely carried out, effectively improving the catalytic performance of the electrode material and reducing the electrode voltage.
[0072] In order to further illustrate the present invention, the electrode material and the preparation method and preparation system provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0073] Example 1
[0074] A preparation system for an electrode material such as Figure 1As shown, it is composed of a winding drum 1, an etching treatment unit 2, a medium-temperature thermal decomposition channel furnace 3, a film casting reaction liquid coating device 8, a high-temperature heat treatment channel furnace 4, a cooling treatment unit 5 and a collection winding drum 6 connected in sequence;
[0075] The etching treatment unit is composed of an etching liquid coating unit 2-1, an etching reaction liquid circulation treatment unit 2-2 and a low-temperature etching channel furnace 2-3 which are arranged in sequence; the etching liquid coating unit 2-1 includes a slit extrusion device and an etching reaction liquid storage tank; one side of the etching reaction liquid circulation treatment unit 2-2 is connected to the slit extrusion device through a pipeline valve; the other side of the etching reaction liquid circulation treatment unit 2-2 is connected to the etching reaction liquid storage tank through a self-priming pump;
[0076] Among them, the low-temperature etching channel furnace 2-3, the medium-temperature thermal decomposition channel furnace 3 and the high-temperature heat treatment channel furnace 4 are provided with an exhaust gas collection channel 7 with a one-way valve;
[0077] The low-temperature etching channel furnace 2-3 has one group of directional wheels arranged horizontally and one group of directional wheels arranged vertically; the medium-temperature thermal decomposition channel furnace 3 has four groups of directional wheels arranged horizontally and one group of directional wheels arranged vertically; the high-temperature heat treatment channel furnace 4 has four groups of directional wheels arranged horizontally and one group of directional wheels arranged vertically.
[0078] Example 2
[0079] A method for preparing an electrode material:
[0080] (1) The nickel-iron foam mesh wound on the winding drum is conveyed at a conveying speed of 2 m / min, and a metal etching reaction liquid with a pH of 1.9 is coated on both sides of the nickel-iron foam mesh by a slit extrusion device in a slit extrusion manner, and the coating thickness of the metal etching reaction liquid on each side is 120 μm, and then enters a low-temperature etching channel furnace (a pair of directional wheels arranged horizontally and a pair of directional wheels arranged vertically) at 75° C. for etching reaction for 15 minutes to obtain a conductive base mesh-metal precursor composite material; wherein the metal etching reaction liquid is composed of cerium nitrate, nickel nitrate, ferric chloride, polyvinyl pyrrolidone and ethylene glycol in a molar ratio of 5:5:3:2:2; the dripping metal etching reaction liquid is collected by an etching liquid coating unit, and is transferred to a metal etching reaction liquid circulation treatment unit for detection and regeneration, and then transported back to the etching reaction liquid storage tank for the next coating of the metal etching reaction liquid;
[0081] (2) conveying the conductive base mesh-metal precursor composite material obtained in step (1) to a medium-temperature thermal decomposition channel furnace (4 pairs of horizontally arranged directional wheels and 1 pair of vertically arranged directional wheels) for in-situ thermal decomposition treatment at 210° C. for 20 minutes to obtain a conductive base mesh-metal heterogeneous layer composite material;
[0082] (3) using a film casting reaction liquid coating device to coat 80 μm of a film casting reaction liquid having a concentration of 20 mM and a pH of 4.5 on both sides of the conductive base mesh-metal heterogeneous layer composite material obtained in step (2) to obtain a film-forming composite; wherein the film casting reaction liquid is composed of a sodium dihydrogen phosphate aqueous solution;
[0083] (4) The biofilm composite obtained in step (3) is transferred to a high-temperature modification treatment channel furnace (4 pairs of directional wheels arranged horizontally and 1 pair of directional wheels arranged vertically) and subjected to high-temperature modification treatment in ammonia at 600° C. for 150 min. After the high-temperature modification treatment is completed, the composite is transferred to a cooling treatment unit to be cooled to room temperature, and is wound up using a collecting winding drum to obtain an electrode material having a heterogeneous layer of a mixture of oxides of three metals, cerium, nickel and iron, and a metal nitride phosphide protective layer symmetrically arranged on both sides of the conductive base mesh.
[0084] Example 3
[0085] A method for preparing an electrode material:
[0086] (1) A 46-mesh twill woven nickel mesh wound on a winding drum is conveyed at a conveying speed of 1.5 m / min, and a metal etching reaction liquid with a pH of 2.2 is coated on both sides of the 46-mesh twill woven nickel mesh by a slit extrusion device in a slit extrusion manner, and the coating thickness of the metal etching reaction liquid on each side is 180 μm, and then enters a low-temperature etching channel furnace (two pairs of directional wheels arranged horizontally and one pair of directional wheels arranged vertically) at 80° C. for etching reaction for 30 minutes to obtain a conductive base mesh-metal precursor composite material; wherein the metal etching reaction liquid is composed of nickel nitrate, ferric nitrate, ferric perchlorate, glucose and propylene glycol in a molar ratio of 3:3:4:2:3, and the extrusion volume of the metal etching reaction liquid is 20 L / min; the dripping metal etching reaction liquid is collected by an etching liquid coating unit, and is transferred to a metal etching reaction liquid circulation treatment unit for detection and regeneration, and then transported back to the etching reaction liquid storage tank for the next coating of the metal etching reaction liquid;
[0087] (2) conveying the conductive base mesh-metal precursor composite material obtained in step (1) to a medium-temperature thermal decomposition channel furnace (four pairs of horizontally arranged directional wheels and one pair of vertically arranged directional wheels) for in-situ thermal decomposition treatment at 200° C. for 30 minutes to obtain a conductive base mesh-metal heterogeneous layer composite material;
[0088] (3) using a film casting reaction liquid coating device to coat 100 μm of a film casting reaction liquid with a pH of 5.5 on both sides of the conductive base mesh-metal heterogeneous layer composite material obtained in step (2) to obtain a film-forming composite; wherein the film casting reaction liquid is composed of a mixed solution of a sodium borate aqueous solution with a concentration of 10 mM and a sodium tungstate aqueous solution with a concentration of 5 mM in a volume ratio of 1:1;
[0089] (4) The biofilm composite obtained in step (3) is transferred to a high-temperature modification treatment channel furnace (three pairs of horizontally arranged directional wheels and one pair of vertically arranged directional wheels) for high-temperature modification treatment in air at 350° C. for 70 minutes. After the high-temperature modification treatment is completed, it is transferred to a cooling treatment unit to cool to room temperature, and is wound up using a collecting winding drum to obtain an electrode material having a heterogeneous layer of a mixture of nickel and iron metal oxides and a boron-tungsten-doped metal oxide protective layer symmetrically arranged on both sides of the conductive base mesh.
[0090] Example 4
[0091] A method for preparing an electrode material:
[0092] (1) conveying a low-chromium stainless steel mesh wound on a winding drum at a conveying speed of 0.6 m / min, coating a metal etching reaction liquid with a pH of 1.6 on both sides of the low-chromium stainless steel mesh by a slit extrusion device, and the coating thickness of the metal etching reaction liquid on each side is 220 μm, and then entering a low-temperature etching channel furnace (two pairs of directional wheels arranged horizontally and two pairs of directional wheels arranged vertically) at 90° C. for etching reaction for 40 minutes to obtain a conductive base mesh-metal precursor composite material; wherein the metal etching reaction liquid is composed of nickel nitrate, cobalt nitrate, ferric perchlorate, ferric dihydrogen phosphate, ethylene glycol and hexadecyltrimethylammonium bromide in a molar ratio of 5:5:7:4:3:3, and the extrusion rate of the metal etching reaction liquid is 15 L / min; using an etching liquid coating unit to collect the dripping metal etching reaction liquid, transferring it to a metal etching reaction liquid circulation treatment unit for detection and regeneration, and transferring it back to an etching reaction liquid storage tank for the next coating of the metal etching reaction liquid;
[0093] (2) conveying the conductive base mesh-metal precursor composite material obtained in step (1) to a medium-temperature thermal decomposition channel furnace (4 pairs of horizontally arranged directional wheels and 1 pair of vertically arranged directional wheels) for in-situ thermal decomposition treatment at 240° C. for 30 minutes to obtain a conductive base mesh-metal heterogeneous layer composite material;
[0094] (3) using a film casting reaction liquid coating device to coat 150 μm of a film casting reaction liquid with a pH of 6.0 on both sides of the conductive base mesh-metal heterogeneous layer composite material obtained in step (2) to obtain a film-forming composite; wherein the film casting reaction liquid is composed of a mixed solution of a sodium phosphate aqueous solution with a concentration of 15 mM and an ammonium molybdate aqueous solution with a concentration of 10 mM in a volume ratio of 1.5:1;
[0095] (4) The biofilm composite obtained in step (3) is transferred to a high-temperature modification treatment channel furnace (two pairs of directional wheels arranged horizontally and three pairs of directional wheels arranged vertically) and subjected to high-temperature modification treatment at 400°C for 35 minutes in a mixed atmosphere of hydrogen sulfide and inert argon gas with a volume ratio of 1:9. After the high-temperature modification treatment is completed, the composite is transferred to a cooling treatment unit to be cooled to room temperature, and is wound up using a collecting winding drum to obtain an electrode material having a heterogeneous layer of phosphorus-bromine-doped oxides of three metals, cobalt, nickel and iron, and a metal phosphorus-molybdenum sulfide protective layer symmetrically arranged on both sides of the conductive base mesh.
[0096] Test Example 1
[0097] The electrode material prepared by the preparation method of Example 2 was used as an electrode for hydrogen production by alkaline water electrolysis of 30% KOH, and was used as a hydrogen evolution electrode. The electrolyte temperature was controlled to be stable at 80°C to perform water electrolysis reaction. The single-chamber voltage of the electrolytic cell was 1.84V@8000A / m 2 , and the electrolysis voltage can be stably maintained at 1.83~1.86V within the specified test time;
[0098] The collected metal etching reaction solution was regenerated by the etching solution circulation treatment unit, and 40 batches of electrode materials were continuously prepared by the preparation method of Example 2. Different batches of electrode materials were used as electrodes for hydrogen production by alkaline water electrolysis of 1M KOH, as oxygen evolution electrodes, and the electrolyte temperature was controlled to be stable at 27°C to carry out hydrogen evolution reaction; the electrochemical workstation was used for detection, and the results obtained were as follows: Figure 2 And as shown in Table 1.
[0099] Table 1 Electrode potential of electrode materials prepared by the preparation method of Example 2 (mV)
[0100]
[0101] from Figure 2 As can be seen from Table 1, the electrode voltages of the 40 batches of electrode materials produced at the same current density are basically the same. It can be seen that the activities of the electrode products obtained by recycling the metal etching reaction solution 40 times are basically the same, which proves that the electrode material prepared by the preparation method of Example 2 has excellent stability and low electrode voltage, and at the same time proves the high utilization of the etching reaction solution by the preparation method.
[0102] Test Example 2
[0103] The difference between Test Example 2 and Test Example 1 is that the test object is the electrode material prepared by the preparation method of Example 3, and it is used as the oxygen evolution electrode, and the rest is the same as Test Example 1; after testing, it is known that the voltage of the single chamber of the electrolytic cell is 1.89V@8000A / m 2, and the electrolysis voltage can be stably maintained at 1.88~1.92V within the specified test time;
[0104] The collected metal etching reaction liquid was regenerated by the etching liquid circulation treatment unit, and 40 batches of electrode materials were continuously prepared by the preparation method of Example 3. Different batches of electrode materials were used as electrodes for hydrogen production by alkaline water electrolysis of 1M KOH, as oxygen evolution electrodes, and the electrolyte temperature was controlled to be stable at 27°C to carry out oxygen evolution reaction; the electrochemical workstation was used for detection, and the results obtained were as follows: Figure 3 And as shown in Table 2.
[0105] Table 2 Electrode potential of electrode materials prepared by the preparation method of Example 3 (mV)
[0106]
[0107]
[0108] from Figure 3 As can be seen from Table 2, the electrode voltages of the 35 batches of electrode materials produced at the same current density are basically the same. It can be seen that the activities of the electrode products obtained by recycling the metal etching reaction solution 35 times are basically the same, which proves that the electrode material prepared by the preparation method of Example 3 has excellent stability and low electrode voltage.
[0109] Test Example 3
[0110] The only difference between Test Example 3 and Test Example 2 is that the test object is the electrode material prepared by the preparation method of Example 4, and the rest is the same as Test Example 2. After testing, it can be found that the voltage of the single chamber of the electrolytic cell is 1.90V@8000A / m 2 , and the electrolysis voltage can be stably maintained at 1.89~1.93V within the specified test time;
[0111] The collected metal etching reaction solution was regenerated by the etching solution circulation treatment unit, and 50 batches of electrode materials were continuously prepared by the preparation method of Example 4. Different batches of electrode materials were used as electrodes for hydrogen production by alkaline water electrolysis of 1M KOH, as oxygen evolution electrodes, and the electrolyte temperature was controlled to be stable at 27°C to carry out oxygen evolution reaction; the electrochemical workstation was used for detection, and the results obtained were as follows: Figure 4 And as shown in Table 3.
[0112] Table 3 Electrode potential of electrode materials prepared by the preparation method of Example 4 (mV)
[0113]
[0114] from Figure 4As can be seen from Table 3, the electrode voltages of the 50 batches of electrode materials produced at the same current density are substantially the same, from which it can be seen that the activities of the electrode products obtained by recycling the metal etching reaction solution 50 times are substantially the same, proving that the electrode material prepared by the preparation method of Example 4 has excellent stability and low electrode voltage.
[0115] Comparative Example 1
[0116] The difference between Comparative Example 1 and Example 3 is that the steps of coating the film casting reaction solution and high-temperature heat treatment are omitted, and the rest is the same as Example 3, to obtain an electrode material having metal heterogeneous layers symmetrically arranged on both sides of the conductive base mesh.
[0117] Comparative test example 1
[0118] The electrode material prepared by the preparation method of Comparative Example 1 was used as an electrode for hydrogen production by alkaline water electrolysis of 30% KOH. When used as an oxygen evolution electrode, the electrolyte temperature was controlled to be stable at 80°C, and the water electrolysis reaction was carried out, and the current density reached 8000A / m 2 When the preparation methods of Example 3 and Comparative Example 1 are used, the changes in the cell electrolysis voltage of the electrode materials prepared are as follows: Figure 5 As shown. Figure 5 It can be seen that the electrode voltage of the electrode material prepared in Example 3 is significantly lower than that of the electrode material prepared by the preparation method of Comparative Example 1, and the stability trend of the electrolysis voltage is significantly better than that of Comparative Example 1, indicating that the electrode material prepared in Example 3 has better catalytic performance and stability.
[0119] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an electrode material, comprising the following steps: (1) coating a metal etching reaction solution on both sides of the conductive base mesh by a slit extrusion method and then performing an etching reaction to obtain a conductive base mesh-metal precursor composite; (2) subjecting the conductive base mesh-metal precursor composite obtained in step (1) to in-situ thermal decomposition to obtain a conductive base mesh-metal heterogeneous layer composite; (3) coating the surface of the conductive base mesh-metal heterogeneous layer composite obtained in step (2) with a film casting reaction solution to obtain a film-forming composite; (4) subjecting the biofilm-forming complex obtained in step (3) to high-temperature modification to obtain an electrode material.
2. The preparation method according to claim 1, characterized in that: The extrusion volume of the slit extrusion in the step (1) is 0.1 to 50 L / min; the running speed of the conductive base mesh is 0.1 to 5 m / min.
3. The preparation method according to claim 1, characterized in that: The coating thickness of the metal etching reaction solution in step (1) is 50 to 250 μm.
4. The preparation method according to claim 1, characterized in that: The metal etching reaction liquid in step (1) comprises a metal salt and a self-thermal decomposition agent; the molar ratio of the metal salt to the self-thermal decomposition agent is (1.3-2):(0.2-3); and the pH of the metal etching reaction liquid is 1.0-3.
0.
5. The preparation method according to claim 4, characterized in that: The metal salt is a mixture of one or more of lanthanum nitrate, cerium nitrate, nickel nitrate, manganese nitrate, chromium nitrate, zirconium nitrate, cobalt nitrate, copper nitrate, vanadium nitrate and zinc nitrate and iron salt; the iron salt is one or more of ferric nitrate, ferric chloride, ferric sulfate, ferric perchlorate and ferric dihydrogen phosphate; the self-thermal decomposition agent is one or more of cyanamide, glycerol, ethylene glycol, glucose, chitosan, polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide.
6. The preparation method according to claim 5, characterized in that: The ratio of the total amount of one or more of lanthanum nitrate, cerium nitrate, nickel nitrate, manganese nitrate, chromium nitrate, zirconium nitrate, cobalt nitrate, copper nitrate, vanadium nitrate and zinc nitrate in the metal salt to the amount of the iron salt is 1:(0.3-1).
7. The preparation method according to claim 1, characterized in that: The film casting reaction liquid in step (3) is an aqueous solution of one or more of sodium phosphate, phosphoric acid, sodium hypophosphite, sodium dihydrogen phosphate, sodium borate, sodium tungstate, and ammonium molybdate.
8. The preparation method according to claim 7, characterized in that: The molar concentration of each solute in the film casting reaction solution is independently 1 to 100 mM, and the pH of the film casting reaction solution is 3.0 to 8.
0.
9. The electrode material prepared by the preparation method according to any one of claims 1 to 8, comprising a metal heterogeneous layer and a protective layer symmetrically arranged in sequence on both sides of a conductive base mesh.
10. The preparation system used in the preparation method according to any one of claims 1 to 8, characterized in that: It includes a winding drum, an etching processing unit, a medium-temperature thermal decomposition channel furnace and a high-temperature thermal treatment channel furnace connected in sequence; The etching processing unit comprises an etching liquid coating unit, an etching reaction liquid circulation processing unit and a low-temperature etching channel furnace which are arranged in sequence; The etching liquid coating unit comprises a slit extrusion device and an etching reaction liquid storage tank.